PROSES PENYUNTINGAN KAMUS PERTANIAN UMUM DI PENERBIT PENEBAR SWADAYA - Selly Ayu Rhahmadani; Irene Maria Juli Astuti (Politeknik Negeri Media Kreatif, 2013)
The purposes of this study are to describe the process of editing, the role of copyeditor, and the difficulty in editing the manuscript of â€œKamus Pertanian Umumâ€. The methods used are a study library, observation, and interviews. The results show thatÂ first, there is a difference house style for writing dictionaries inÂ PenebarÂ SwadayaÂ andÂ second, the role of copy editor is only involved in mechanical editing.